PEMBELAJARAN GENRE TULIS DALAM SISTEM PERSEKOLAHAN INDONESIA DI SUMATRA UTARA - Amrin Saragih; Isli Pane (Metalingua: Jurnal Penelitian Bahasa, 2016)
THE objectives of the study are to describe written genres acquired by schoollearners (SD, SMP and SMA) in North Sumatra Province (referred to as the NSlearners) and propose a genre-baased learning model in accordance with the2013 Curriculum. This is a qualitative study. The subjects were 1025 learnersand 18 teachers comprising those representing SD (6), SMP (6) and SMA (6)and parents of the learners in 18 schools. The data were the learners' writtentexts or genres, descriptions of learning genres in the class-rooms, transcriptionsof interviews with the teachers and parents gained by data elicitation, observations and interviews. The learners' written texts were analyzed using systemic functional linguistics (SFL) theories. The data obtained from observations and interviews were analyzed using qualitative data analysis techniques. The findings show that firstly the learners have already acquired ten kinds of basic genres, namely description, report, recount, narrative, anecdote, exemplum, observation, procedure, exposition, and discussion, and also they were able to write multiple genres. Secondly, some elements of the school social context such as the techers' limited competence and skills on genres became a hindrance in teaching the written genre. Thirdly, to overcome such hindrance a model for genre learning was developed. The model was a combination of the genre-based langugae learning and the scientific approach feature of the 2013 Curriculum. Such learning model is effective for written genre learning.AbstrakKAJIAN ini bertujuan mendeskripsi capaian genre tulis oleh pemelajar sekolah (SD, SMP, SMA) di Sumatra Utara (selanjutnya dirujuk sebagai pemelajar SU) dan mengajukan model pembelajaran berdasarkan genre-based language learning yang sejalan dengan Kurikulum 2013 berdasarkan perolehan genre itu. Desain penelitian adalah deskriptif kualitatif. Sumber data adalah 1025 pembelajar dan 18 guru, yang terdiri atas guru SD (6), guru SMP (6), dan SMA (6), serta orang tua pemelajar dari ke-18 sekolah (SD, SMP dan SMA) itu. Data kajian ini adalah teks atau genre yang ditulis pembelajar SU, deskripsi pembelajaran genre di kelas, dan transkripsi wawancara dengan guru dan orang tua yang masing-masing diperoleh dengan teknik elisitasi data, observasi pembelajaran menulis genre di kelas, dan wawancara dengan guru dan orang tua. Teks yang ditulis pemelajar dianalisis dengan menggunakan teori linguistik fungsional sistemik (LFS). Data dari observasi dan wawancara dianalisis dengan menggunakan teknik analisis data kualitatif. Temuan penelitian adalah pertama, pemelajar SU telah memperoleh dan mampu menulis sepuluh jenis genre tunggal, yakni deskripsi, laporan, recount, narasi, anekdot, exemplum, observasi, prosedur, eksposisi, dan diskusi, serta mereka mampu menulis genre kompleks. Kedua, ditemukan bahwa sebagian unsur konteks sosial persekolahan berupa keterbatasan pengetahuan dan ketrampilan guru tentang genre dan pembelajaran berbasis teks telah menjadi penghambat dalam pembelajaran menulis genre. Ketiga, sekaitan dengan itu model pembelajaran genre dikemukakan. Model pembelajaran genre tulis yang diajukan merupakan gabungan dari genre-based language learning dan pendekatan ilmiah yang menjadi ciri utama Kurikulum 2013. Model ini efektif untuk pembelajaran genre tulis.